Leserbrief zum Beitrag MRg-HIFU (doi:10.1055/a-0817-5645) - Holger Strunk; Tolga Tonguc; Milka Marinova (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2019)
Matrix metalloproteinases (MMPs) play critical roles in wound repair, yet their context-dependent functions in diabetic wound healing remain elusive. In this study, we found that both the expression and activity of MMP14 were significantly elevated in diabetic foot ulcers (DFUs). Using animal models, we further revealed the dual roles of MMP14 in wound healing. In normal rats, inhibition of MMP14 delayed wound closure, confirming its supportive role in physiological tissue repair. In contrast, in diabetic rats, pathologically increased MMP14 levels impaired healing, whereas moderate inhibition significantly accelerated wound repair. Among the inhibitors tested, the selective MMP14 inhibitor NSC405020 produced the most favorable therapeutic effect in diabetic wounds, markedly enhancing healing rates and collagen deposition at a concentration of 1 mg/mL. Compared with the broad-spectrum MMP inhibitor ND336, NSC405020 demonstrated therapeutic safety and comparable efficacy without notable toxicity in a rat model. Collectively, these findings elucidate the context-dependent role of MMP14 in wound healing, suggesting that MMP14 may be a promising therapeutic target for diabetic wound healing. Therefore, our study provides a theoretical foundation for the development of effective and safe treatments for diabetic wound management.